Investigation of coupling efficiency in laser beam welding of copper materials using brilliant infrared and green laser radiation - Kaufmann, Florian; Möttingdörfer, Robert; Roth, Stephan; Schmidt, Michael (Journal of Manufacturing Processes, 2024)
One of the fundamental effects of laser material processing is laser beam absorption. The absorptivity in the laser welding process is subjected to temporal and spatial fluctuations due to temperature and phase changes and is furthermore dependent on the wavelength used. Currently, experimental absorptivity data for copper at high temperatures is rarely available, and discussions of investigation are largely based on theoretical assumptions. However, this property is essential for a fundamental understanding of the phenomena involved in laser-matter interaction and for efficient process design, especially for the emerging manufacturing processes for electric vehicles, where copper materials are widely used. In this work, a specially designed, low-cost experimental arrangement was built to measure the laser absorption during the process in different welding modes, which enables the derivation of coupling efficiency values in these regimes. Brilliant laser beam sources with λ = 515 nm and λ = 1030 nm radiation and comparable spot characteristics on the workpiece were used for the investigation. Results captured with microsecond resolution show several important features, including the points of melting and vapor capillary formation for both pulsed and continuous process guiding. General tendencies known from literature could be confirmed by our measurements, and the comparison of the absorptivity data with microscopic inspection and a weld seam cross-sectional analysis shows a significant correlation of the characteristics.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Absorptivity; Copper; Energy coupling; EV manufacturing; Green laser radiation; Laser beam welding